1983
DOI: 10.1073/pnas.80.7.1982
|View full text |Cite
|
Sign up to set email alerts
|

Cellular myc oncogene is altered by chromosome translocation to an immunoglobulin locus in murine plasmacytomas and is rearranged similarly in human Burkitt lymphomas.

Abstract: Molecular cloning has recently established that the 15;12 chromosome translocations in murine plasmacytomas fuse DNA from chromosome 15 to the immunoglobulin heavy (H) chain locus, usually within the switch recombination region near the a constant region gene. We show here that the incoming DNA bears the cellular gene (c-myc) homologous to the oncogene (vnmyc) of avian retrovirus MC29. In human Burkitt lymphomas bearing an 8;14 translocation, c-myc was also rearranged, apparently (in at least two cases) to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(116 citation statements)
references
References 41 publications
5
109
0
2
Order By: Relevance
“…The unrearranged c-myc gene is still present in Manca cells, but our preliminary results from use of Northern probes (probe 2 in Figure 1), S 1 mapping and cDNA cloning indicate that this allele is barely, if at all, expressed. Such a situation has already been reported for a mouse plasmacytoma and may be true for other Burkitt's lymphomas 11,32,34 . Hence, transcriptional activation of the c myc gene appears to be an important result of translocation and in the case described here, it is possible that such activation is largely contributed to by the immunoglobulin heavychain locus enhancer.…”
Section: Multiple Mechanisms Of C-myc Activationsupporting
confidence: 65%
See 4 more Smart Citations
“…The unrearranged c-myc gene is still present in Manca cells, but our preliminary results from use of Northern probes (probe 2 in Figure 1), S 1 mapping and cDNA cloning indicate that this allele is barely, if at all, expressed. Such a situation has already been reported for a mouse plasmacytoma and may be true for other Burkitt's lymphomas 11,32,34 . Hence, transcriptional activation of the c myc gene appears to be an important result of translocation and in the case described here, it is possible that such activation is largely contributed to by the immunoglobulin heavychain locus enhancer.…”
Section: Multiple Mechanisms Of C-myc Activationsupporting
confidence: 65%
“…Adrian C. Hayday, Stephen D. Gillies recently been shown that the c-myc gene is translocated into an immunoglobulin locus in certain lymphoid neoplasms of both mice and men [7][8][9][10][11][12] . Thus, murine c-myc gene is recombined into the immunoglobulin heavy-chain locus in BALBIc plasmacytomas characterized by t(12:15) translocations 7,[9][10][11] .…”
Section: Authorsmentioning
confidence: 99%
See 3 more Smart Citations